An Assessment of Tenants Satisfaction in Students Hostels in Awka - Uche, J. C.; Ezeanwu, G. E.; Onyejiaka, J. C. (International Journal of Real Estate, 2025)
Students’ hostels play a crucial role in providing accommodation for students pursuing higher education in any part of the world. The growing student population in Awka, Anambra State in Nigeria due to the presence of Nnamdi Azikiwe University and other notable tertiary institutions, has increased the demand for quality housing in tertiary institutions. Currently hostels face issues of safety, quality, and affordability, affecting students, academic success and well-being. Despite Tetfund's plans to construct new hostels in 2024, only 15% of students live on campus, facing security risks and high off-campus costs. The research aim was to provide an assessment of tenants’ satisfaction in student hostels within and around Nnamdi Azikiwe University Awka, Nigeria. The research objectives include: to establish categories of student hostels in Awka, to assess the current level of tenant satisfaction in different students hostels in Awka, to identify factors influencing tenant satisfaction in students hostels in Awka and to identify areas of improving the level of tenant satisfaction in students hostels in Awka. The scope of the study was limited to coverage of public and private hostels within and outside Nnamdi Azikiwe University, Awka. The population of the study is a total number of public and private hostels in Awka.  The study adopted research survey method to elicit data from students, hence primary and secondary data was used for the research study. Taro Yamane formula was used to determine the sample size for both public and private hostel. 366 questionnaire were distributed and 337 was retrieved representing 92.7% responses.  Findings revealed that the facilities amongst those living in private hostels had 20.5% basic setups, 35.3% had standard accommodations, and 8.0% enjoy premium conditions. Conversely, Public hostels exhibit a higher proportion of basic facilities (23.7%), but fewer students (11.6%) have standard amenities, and only 0.9% have access to premium facilities. Key areas of dissatisfaction includes room size layout, hygiene issues, facilities quality etc. To improve tenant satisfaction in students hostels, the study recommended areas for improvement for both private and public hostels which include increasing room comfort, ensuring cleanliness and hygiene, bolstering safety and security, upgrading furniture quality, minimizing noise levels, providing reliable utilities and effective management practices such as establishing clear hostel policies and balanced tenancy agreements and flexibility in visiting hours for public hostels.
Keywords: Student’s hostels; assessment; tenant satisfaction; Nnamdi Azikiwe University; Awka